Kualifikasi Justice Collaborator Dalam Perkara Tindak Pidana Korupsi (Studi Putusan Pengadilan Negeri Jakarta Pusat Nomor 48/Pid.Sus-TPK/2020/PN Jkt Pst) - Saliu, Abdul Rahman; Supusepa, Reimon; Fadillah, Astuti Nur (MATAKAO Corruption Law Review, 2024)
Introduction: The law enforcement process has several stages, one of the most decisive in eradicating crime is the criminal justice system. There are several terms used in the judicial process, one of which is Justice Collaborator which is regulated in several regulations including Article 10 A paragraph (1) jo, paragraph 3 Law No. 31 of 2014 concerning PSK which in essence provides an explanation that "witnesses of perpetrators can be given awards for the testimony given in the form of: leniency in criminal sentences (covering criminal penalties, special conditional sentences, or the lightest punishment among other defense attorneys), conditional sentences , additional remissions and other compensation rights in accordance with statutory provisions for perpetrator witnesses who have driver status. Purposes of the Research: Juridically analyze the qualifications of justice collaborators in corruption crimes. Methods of the Research: The method used in this research is normative juridical using a statutory and regulatory approach and contextual approach. Results of the Research: The Justice Collaborator status given to a suspect or defendant or even a convict will have a big impact on him. One of the well-known cases of the application of Justice Collaborator was in the criminal case of bribery for the election of deputy governor of Bank Indonesia which ensnared 26 members of the people's representative council. Agus Condro, who is a criminal and Justice Collaborator, Agus Condro was sentenced to a lighter sentence than the prosecutor demanded. The judge's considerations in sentencing defendant Tommy Sumardi, who has the status of Justice Collaborator in the case of removing Djoko Tjandra's red notice status, defendant Tommy Sumardi was sentenced to prison for 2 (two) years and a fine of Rp. 100,000,000.00 (one hundred million rupiah).) subsidiary 6 (six) months in prison. Imprisonment sentences and fines are higher than those charged by the public prosecutor.